Monsoon : the Indian Ocean and the future of American power - Kaplan, Robert D., 1952- (New York : Random House, 2010)
In "Monsoon," a pivotal examination of the Indian Ocean region and the countries known as "Monsoon Asia," bestselling author Robert D. Kaplan deftly shows how crucial this dynamic area has become to American power in the twenty-first century. Kaplan also offers riveting insights into the economic and naval strategies of China and India and how they will affect U.S. interests, while also providing an on-the-ground perspective on the more volatile countries in the region.
Keywords: National security -- United States; National security -- Indian Ocean Region; United States -- Foreign relations -- Indian Ocean Region; Indian Ocean Region -- Foreign relations -- United States; Indian Ocean Region -- Strategic aspects